Cerebellothalamocortical pathway abnormalities in torsinA DYT1 knock-in mice - Uluğ, Aziz M. (National Academy of Sciences, 2011)
The factors that determine symptom penetrance in inherited disease are poorly understood. Increasingly, magnetic resonance diffusion tensor imaging (DTI) and PET are used to separate alterations in brain structure and function that are linked to disease symptomatology from those linked to gene carrier status. One example is DYT1 dystonia, a dominantly inherited movement disorder characterized by sustained muscle contractions, postures, and/or involuntary movements. This form of dystonia is caused by a 3-bp deletion (i.e., ΔE) in the TOR1A gene that encodes torsinA. Carriers of the DYT1 dystonia mutation, even if clinically nonpenetrant, exhibit abnormalities in cerebellothalamocortical (CbTC) motor pathways. However, observations in human gene carriers may be confounded by variability in genetic background and age. To address this problem, we implemented a unique multimodal imaging strategy in a congenic line of DYT1 mutant mice that contain the ΔE mutation in the endogenous mouse torsinA allele (i.e., DYT1 knock-in). Heterozygous knock-in mice and littermate controls underwent microPET followed by ex vivo high-field DTI and tractographic analysis. Mutant mice, which do not display abnormal movements, exhibited significant CbTC tract changes as well as abnormalities in brainstem regions linking cerebellar and basal ganglia motor circuits highly similar to those identified in human nonmanifesting gene carriers. Moreover, metabolic activity in the sensorimotor cortex of these animals was closely correlated with individual measures of CbTC pathway integrity. These findings further link a selective brain circuit abnormality to gene carrier status and demonstrate that DYT1 mutant torsinA has similar effects in mice and humans.